PENERAPAN TEKNIK PROBING-PROMPTING DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS X SMK TI GARUDA NUSANTARA CIMAHI - Elis Nurhayati (Departement of Mathematics Education, 2019)
The ability of understanding is the important ability in the science development. The ability of mathematical communication is expected can increase simultaneously by the development of the science and technology. Nevertheless, the implementation of mathematical learning still focuses to the teacher, this method makes students cannot develop their ability in mathematical communication. Their report study in mathematics is still under minimum completeness criteria (KKM), namely 75. One of the recommended effort to deal with this condition is the using probing-prompting technique. The aim of this research is knowing the impact of the enhancement of student’s ability in mathematical understanding using probing-prompting technique rather than are compared with project base learning learning technique. The result of this research show that student’s ability of mathematical communication using probing-prompting technique is better than technique with α = 0,05. To conclude, probing-prompting technique can increase student is ability in mathematical understanding